2021
DOI: 10.1155/2021/6678364
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of 0.19 mg Fluocinolone Acetonide Intravitreal Implant: A Systematic Review

Abstract: Corticosteroids are used in a variety of ophthalmological diseases. One challenge faced by ophthalmologists is to deliver corticosteroids to the posterior segment of the eye with efficacy and safety. Sustained-release corticosteroid implants may be the answer to this problem. The 0.19 mg fluocinolone acetonide (FAc) implant (Iluvien®) releases FAc for 36 months, and it is approved for the treatment of diabetic macular edema (DME) and noninfectious uveitis. We decided to do a systematic review to acknowledge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Inconsistent reporting of outcomes and adverse events between studies limited our conclusions and motivated the decision to group adverse events such as IOP elevation, ocular hypertension, and glaucoma progression together. Additionally, there was a lack of RCTs reporting on fluocinolone acetonide, which has been less associated with IOP spikes and has improved VA outcomes with off-label use [32]. The proportion of phakic patients at final follow-up was not reported in the individual studies and could not be captured in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent reporting of outcomes and adverse events between studies limited our conclusions and motivated the decision to group adverse events such as IOP elevation, ocular hypertension, and glaucoma progression together. Additionally, there was a lack of RCTs reporting on fluocinolone acetonide, which has been less associated with IOP spikes and has improved VA outcomes with off-label use [32]. The proportion of phakic patients at final follow-up was not reported in the individual studies and could not be captured in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4 It was approved for ME treatment related to diabetes or noninfectious uveitis. 5 Neuroprotective properties of intravitreal FAc was studied in rats by Glybina et al 7 They showed that its sustained release could represent a therapeutic means in the future to manage RP patients by protecting photoreceptors and thereby reduce retinal degeneration. However, to date, no data have been reported on the effect of FAc implant in RP cases with ME.…”
Section: Discussionmentioning
confidence: 99%
“…3 Intraocular administrations of steroids (either triamcinolone acetonide or dexamethasone implant) have further been proposed, and demonstrated promising results in some cases. 4 Recently, fluocinolone acetonide (FAc) implant (Iluvien®, Alimera Sciences, GA) was approved both for diabetic macular edema (DME) or noninfectious uveitis, 5 demonstrating a sustained effect up to three years. Its extended effectiveness had led to FAc off-label use in many other steroid-dependent retinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As life expectancy rises, the prevalence of these diseases is on the ascent, posing a challenge for ophthalmologists given their substantial impact on the quality of life for affected individuals. [10] Non-Hodgkin's lymphoma (NHL), the most prevalent hematological malignancy globally, encompasses a diverse spectrum of B-cell and T-cell proliferations [11]. Trophoblasts represent the initial cells embarking on a sophisticated differentiation program.…”
Section: Introductionmentioning
confidence: 99%